Culturally Imprinted Anxiety and the Itinerary of Clinical Trial Projects for Its Management - Malik, Tariq H. (Cross-cultural research, 2021)
Anxiety has become ubiquitous in modern life, across countries. Cultural theories suggest that high uncertainty avoidance (UA) increases anxiety, while long-term orientation (LTO) decreases it. We question whether a high UA culture in a region attracts research and development (R&D) projects regarding anxiety management, compared to LTO. Furthermore, do these opposite dimensions moderate each other in attracting a pharmaceutical firm’s response? This article explores this link between the UA culture and the moderation effect of LTO. Using data on clinical trials related to anxiety management projects in 67 countries, we record 10,585 observations, capturing 4% of the global population of clinical trials on the subject. We find that the uncertainty avoidance index (UAI) shows a negative correlation with the intensity of the anxiety management project, while LTO has no significant correlation. The interaction between the two shows positive correlation. The results are found to be significant after controlling for confounding variables and robustness checks. This study makes three contributions. First, it highlights the link between culture and anxiety management projects through the clinical trial movement. Second, it contributes to cultural theory, suggesting that the UAI defines problems and LTO defines innovative solutions. It also highlights the differences and links between the UAI and LTO at the conceptual level. Thirdly, it offers general policy and practical implications.